PENGARUH PENGGUNAAN GADGET TERHADAP PENDIDIKAN KARAKTER PESERTA DIDIK DI ERA GLOBALISASI - Nurul Kamilah, Zahidah; Rahmah Azzahra, Siti; Ul Jannah, Yunita; Natasya, Rufaidah; Wahyudin, Dede; Caturiasari, Jennyta (JURNAL SINEKTIK, 2025)
A gadget is a digital technology in the era of globalization that has an active role in social life and has a significant influence, especially on students who use it. Because gadgets are easily available at an affordable price, they can be tailored to the needs of their users, so there are various features that can be used. This study was conducted to determine the responses of respondents related to the effect of gadget use on the character education of students in the era of globalization. This method is carried out in research using questionnaires and literature studies. There were 80 respondents, consisting of 8 students (10%), 15 teachers (18.18%), 39 students (48.8%), 5 housewives (6.3%), and 13 members of the general public (16.2%). Based on the results of the questionnaire, the use of gadgets by students affects their character education; they tend to be more apathetic, have an irrational mindset, and lack sympathy. In addition, students often leave their obligations, namely worship, because they are too engrossed in using their gadgets.Â